Penerapan Konsep Kesehatan Jiwa Imam Al-Ghazali Dalam Bimbingan Dan Konseling Islam - M.Yoga Pratama Harahap; Hendra Hendra (Universitas Dian Nuswantoro, 2022)
Mental health is a vital development factor and a national goal. Citizens of a country who are mentally healthy are expected to be able to contribute actively to the society in which they live. In an ideal state of mental health, a person is not only physically, mentally, spiritually and socially healthy, but also has the potential to lead a fruitful life. However, in reality, many different mental health problems exist in life. This study aims to discuss mental health in the perspective of the teachings of Imam Al-Ghazali. This investigation is a literary analysis based on textual analysis techniques using the literature review method. Mental health is seen as a model that includes adherence to one's religious beliefs, freedom from mental illness, development of a mature worldview, development of positive social relationships, and the desire for material and spiritual success. This article examines various approaches to mental health inspired by Imam Al-Ghazali that can be adapted to individual needs for guidance and support. The benefits of incorporating mental health concepts into training and counseling are explored in detail.